Inequality and voting in fragile countries: Evidence from Mozambique - Margherita Bove; Eva-Maria Egger; Sam Jones; Patricia Justino; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The political consequences of economic inequality have been debated in academic and policy circles for centuries. The nature of this relationship seems highly dependent on specific contexts, with empirical studies showing mixed evidence on how economic inequality affects voting and other forms of political participation. This evidence is largely driven by advanced democracies. We have to date limited knowledge on how economic inequality affects how individuals and groups vote in developing and weaker states even though such evidence is central to understanding how democracy might be consolidated in such settings. This paper addresses this question in the case of Mozambique, one of the poorest countries in the world. Contrary to initial theoretical predictions, we find evidence for a positive association between voter turnout and inequality in rural areas, in particular across the poorest localities and in localities where both wealth and inequality increased. While tempting to see this result as a political response of the poorest to inequality, reflections on the Mozambique context point towards elite capture as the most likely explanation for this result. We find no effect of inequality on political competition. In line with prior theoretical expectations, we find a negative association between inequality and voting for the incumbent party, in localities where wealth and inequality simultaneously increased and in the centre region.
Keywords: D31; D72; O55; 330; economic inequality; voting; elections; developing countries; Mozambique